Sphingosine kinase inhibition ameliorates chronic hypoperfusion-induced white matter lesions. (March 2016) - Yang, Ying; Torta, Federico; Arai, Ken; Wenk, Markus R.; Herr, Deron R.; Wong, Peter T.-H.; Lai, Mitchell K.P.
Abstract: White matter lesions (WML) are thought to contribute to vascular cognitive impairment in elderly patients. Growing evidence show that failure of myelin formation arising from the disruption of oligodendrocyte progenitor cell (OPC) differentiation is a cause of chronic vascular white matter damage. The sphingosine kinase (SphK)/sphingosine-1-phosphate (S1P) signaling pathway regulates oligodendroglia differentiation and function, and is known to be altered in hypoxia. In this study, we measured SphK, S1P as well as markers of WML, hypoxia and OPC (NG2) in a mouse bilateral carotid artery stenosis (BCAS) model of chronic cerebral hypoperfusion. Our results indicated that BCAS induced hypoxia inducible factor (HIF)-1α, Sphk2, S1P, and NG2 up-regulation together with accumulation of WML. In contrast, BCAS mice treated with the SphK inhibitor, SKI-II, showed partial reversal of SphK2, S1P and NG2 elevation and amelioration of WML. In an in vitro model of hypoxia, SKI-II reversed the suppression of OPC differentiation. Our study suggests a mechanism for hypoperfusion-associated WML involving HIF-1α-SphK2-S1P-mediated disruption of OPC differentiation, and proposes the SphK signaling pathway as a potential therapeutic target for white matter disease. Highlights: White matter lesions (WML) are thought to contribute to vascular cognitive impairment in elderly patients, and may be related to disruption of oligodendrocyte progenitor cell (OPC) differentiation resulting in failure of myelin sheath formation. Oligodendroglia differentiation and function is regulated by sphingosine kinase (SphK)/sphingosine-1-phosphate (S1P) mediated signaling pathways which are known to be altered in hypoxia. A mouse bilateral carotid artery stenosis (BCAS) model of chronic cerebral hypoperfusion showed hypoxia inducible factor (HIF)-1α, Sphk2, S1P, and OPC marker NG2 up-regulation together with accumulation of WML. Co-treatment of BCAS with the SphK inhibitor, SKI-II showed partial reversal of SphK2, S1P and NG2 elevation and amelioration of WML. In a chemical model of hypoxia, SKI-II reversed the suppression of OPC differentiation in vitro. The HIF-1α-SphK2-S1P-mediated disruption of OPC differentiation may be a potential therapeutic target for white matter disease.